2010
DOI: 10.1016/j.devcel.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Growth-Stabilizing Regulatory Feedback Mechanism between Myc and Yorkie, the Drosophila Homolog of Yap

Abstract: Summary An understanding of how animal size is controlled requires knowledge of how positive and negative growth regulatory signals are balanced and integrated within cells. Here we demonstrate that the activities of the conserved growth promoting transcription factor Myc and the tumor-suppressing Hippo pathway are co-dependent during growth of Drosophila imaginal discs. We find that Yorkie (Yki), the Drosophila homolog of the Hippo pathway transducer, Yap, regulates the transcription of Myc, and that Myc func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
254
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(269 citation statements)
references
References 50 publications
13
254
2
Order By: Relevance
“…This result is striking because overexpression of Myc in wild-type cells did not cause up-regulation of ex-lacZ expression; rather, it slightly suppressed ex-lacZ expression levels (Fig. 4 B and D) (25). This indicates that the increase of Yki activity in scrib − +Myc clones is an indirect consequence of these cells being able to evade cell competition due to the increased fitness conferred by Myc overexpression, rather than Myc directly inducing Yki activity.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…This result is striking because overexpression of Myc in wild-type cells did not cause up-regulation of ex-lacZ expression; rather, it slightly suppressed ex-lacZ expression levels (Fig. 4 B and D) (25). This indicates that the increase of Yki activity in scrib − +Myc clones is an indirect consequence of these cells being able to evade cell competition due to the increased fitness conferred by Myc overexpression, rather than Myc directly inducing Yki activity.…”
Section: Resultsmentioning
confidence: 51%
“…Elevation of Yki levels is sufficient to protect M +/− cells from cell competition and can even transform normal cells into supercompetitors (22,24,25). Remarkably, ex-lacZ, which was up-regulated in noncompeted scrib − clones, was not induced in scrib − clones surrounded by wild-type cells in most regions of eye and wing discs (Figs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We also provided evidence that tissue damage may regulate dMyc expression at a post-transcriptional level. Two recent studies suggest that Yki-Sd may directly regulate dMyc transcription in wing imaginal discs [33,34]. We identified a 1 kb dMyc enhancer (dMyc1.0) that contains multiple consensus Sdand Stat-binding sites and is capable of mediating the transcriptional regulation of a reporter gene (dMyc1.0-luc) by Yki-Sd and Stat in S2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway also inhibits expression of a microRNA bantam to affect organ size, although the downstream effector of bantam is not clear. Furthermore, Yki-Sd was shown to transcriptionally induce dMyc, a potent promoter of ribosome biogenesis and cell growth (Neto-Silva et al, 2010;Ziosi et al, 2010), which may mediate the cell competition phenomenon observed in tissues with imbalance of Hippo pathway activity. In addition, Yki induces E2F1 (Goulev et al, 2008), which may be involved in cell-autonomous regulation of cell proliferation; the EGFR ligands Vein, Keren, and Spitz (Zhang et al, 2009b;Ren et al, 2010); the Jak/Stat pathway ligands Unpaired1/2/3 (Upd1/2/3) (Karpowicz et al, 2010;Ren et al, 2010;Shaw et al, 2010;Staley and Irvine, 2010), which could mediate non-cell-autonomous function of the Hippo pathway; and the Hippo pathway genes Ex, Kibra, Crb, and Fj (Cho et al, 2006;Hamaratoglu et al, 2006;Genevet et al, 2009;Genevet et al, 2010), which may constitute a signal feedback loop.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%